The evolution of abnormally coarse grain structures in beta-annealed Ti-6Al%-4V% rolled plates, observed by in-situ investigation. (December 2021) - Byres, Nicholas E.; da Fonseca, Joao Quinta; Daniel, Christopher S.; Donoghue, Jack; Davis, Alec E.; Shanthraj, Pratheek; Dod, Benjamin; Prangnell, Philip B.
Graphical abstract: Abstract: The factors controlling the evolution of abnormally coarse grain (ACG) structures during standard β annealing of titanium-6Al%-4V% (Ti64) hot-rolled plates, have been investigated in more detail than previously, using both ex-situ through-thickness large area, and in-situ EBSD micro-texture observation. Starting with a typical, through thickness, α + β deformation texture distribution that gives rise to ACGs at the plate mid-section, each stage of the annealing process has been sequentially characterised and phenomenologically linked to the spatial texture evolution that occurs during transient heating through the α → β phase transformation and the subsequent isothermal hold at the β-annealing temperature. It was found that during the ramp heating phase, the rotated cube texture component greatly expands from just below the β transus by broad front strain induced boundary migration (BF-SIBM), driven by a disparity in stored energy with neighbouring texture bands from the α and γ fibres. This subsequently sets up the necessary conditions for unstable coarsening of surviving grain clusters with predominately near α fibre orientations during the super-transus hold, in a process with similar characteristics to discontinuous recrystallisation. Humphreys' mean field model of the stability of cellular microstructures, effectively explains the process by which these grain clusters, which have a lower misorientation range relative to the rotated cube component matrix, have a higher probability of entering a discontinuous growth regime, compared to other components from the α and γ fibres. Furthermore, the conditions that give rise to the development of ACG structures could be linked to the high strain rate and temperature experienced at the central mid-thickness of rolled plates.